Cocconeis rouxii Héribaud & Brun a forgotten, but common benthic diatom species from the Massif Central, France. Issue 2 (3rd April 2019) - Wetzel, Carlos E.; Beauger, Aude; Ector, Luc
ABSTRACT: Cocconeis rouxii was decribed by J.Héribaud & J.Brun from samples collected in mountainous freshwater sources in the Auvergne region, France. Despite being mentioned in earlier publications and classical European floristic books, this species has never been fully explained. Its morphology is poorly known, as it has confusing and sparse citations in the literature, despite being abundant in several samples from the Massif Central. Some inconclusive attempts to investigate the original gatherings during the 1980s, and the exclusion of the taxon in major floristic works, led to the almost complete abandonment of the name. We here detail with light and scanning electron microscopy one population found in the source Bernadette, located near its type locality. The species seems to be quite common in several regions of France with metamorphic geological properties (i.e. crystalline rocks).